-2r+-7=-6

Simple and best practice solution for -2r+-7=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2r+-7=-6 equation:


Simplifying
-2r + -7 = -6

Reorder the terms:
-7 + -2r = -6

Solving
-7 + -2r = -6

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -2r = -6 + 7

Combine like terms: -7 + 7 = 0
0 + -2r = -6 + 7
-2r = -6 + 7

Combine like terms: -6 + 7 = 1
-2r = 1

Divide each side by '-2'.
r = -0.5

Simplifying
r = -0.5

See similar equations:

| 2q-8=2 | | 36+72+X=183 | | 3j+8=-10 | | 2j+7=4 | | 1=0t+.5*9.8*t*t | | 4f-12=4 | | 10=4+2m | | 10=4m+2 | | 2s-(-2)=18 | | 9x=x | | 8x-8x+8x-8x+8x=0 | | Vf=Vo+2ax(a) | | 2y+4z+6=0 | | Vf=Vo+2ax | | 29-4x=14-9 | | 2x^2-y^2=2 | | 2x+10=-10-2x | | 3a-2bi=6-8i | | 90+3=7x+4 | | y=-x^2+6x+10 | | 22+8t+6t-16=19t+11-5t-5 | | 4p-7=3p+6 | | 4x+8y-3x+2= | | 10-x=-8 | | 5+5(x+2)+3x^2=4+3(2x-6)+3x^2 | | 2+12x=-20+x | | x*3+30=75 | | 3p+8=11+2p | | (x+y+x)dx-(y+x^2y)dy=0 | | 2x-18y=PR | | 37/7= | | m-48=13 |

Equations solver categories